The Potential and Integration of Nusantara Games as a Multicultural Approach in Guidance and Counseling - Moch. Syihabudin Nuha; Rosyid Arfan Gustama; Erfan Nawawi; Muh. Nur Alamsyah; M. Yusuf (Journal of Cultural Guidance and Counseling, 2025)
The cultural and traditional diversity found in Indonesia has given rise to various innovations in many fields. One of these is the traditional games of the Nusantara. These games, in relation to guidance and counseling, carry meaningful and relevant social, emotional, and spiritual values in the context of individual development. This study aims to explore the potential of Nusantara games as an alternative medium in a multicultural counseling approach. The research method used is a literature review through literature search, identification and selection of literature, synthesis analysis and evaluation of selected literature, drawing conclusions, and discussing the results of the review. Through a qualitative approach, this study analyzes the integration of Nusantara games in multicultural counseling. Ten Nusantara games were identified, including their general characteristics, related aspects, and effectiveness based on previous research. The findings indicate that Nusantara games have interrelated aspects in individual development, including personal, social, learning, and career aspects. The utilization of Nusantara games is important both as a means of cultural preservation and as a strategic approach in the counseling process. This study has limitations on the variety of games that do not include all kinds of traditional games in Indonesia, and only focuses on the potential and integration of games as a multicultural approach in Guidance and Counseling. The implications of these findings support the integration of Nusantara games as contextual and adaptive facilitators in counseling services.